2008
DOI: 10.1371/journal.pone.0002550
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Caenorhabditis elegans Locomotion in a Structured Microfluidic Environment

Abstract: BackgroundBehavioral studies of Caenorhabditis elegans traditionally are done on the smooth surface of agar plates, but the natural habitat of C. elegans and other nematodes is the soil, a complex and structured environment. In order to investigate how worms move in such environments, we have developed a technique to study C. elegans locomotion in microstructures fabricated from agar.Methodology/Principal FindingsWhen placed in open, liquid-filled, microfluidic chambers containing a square array of posts, we d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
160
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 142 publications
(169 citation statements)
references
References 17 publications
8
160
0
1
Order By: Relevance
“…A bulk modulus~1 atm would lead to observable strains (~10% if the worm moves downwards a distance of 1 m in the water column), suggesting that a soft, hydraulically reinforced body plan may allow the worm to inhabit a greater range of environments. Similarly, a soft, isotropically deformable body may allow the worm to optimize its swimming mechanism for heterogenous or pressurized environments, as there is known mechanical feedback between the worm's environment and its ability to swim (13,53).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A bulk modulus~1 atm would lead to observable strains (~10% if the worm moves downwards a distance of 1 m in the water column), suggesting that a soft, hydraulically reinforced body plan may allow the worm to inhabit a greater range of environments. Similarly, a soft, isotropically deformable body may allow the worm to optimize its swimming mechanism for heterogenous or pressurized environments, as there is known mechanical feedback between the worm's environment and its ability to swim (13,53).…”
Section: Discussionmentioning
confidence: 99%
“…One such intermediate system is the multicellular round worm Caenorhabditis elegans, a widely studied model organism. The importance of C. elegans mechanics is highlighted by previous studies suggesting that the worm's locomotory patterns and foraging behaviors are strongly dependent on mechanical and osmotic stresses (13)(14)(15). Indeed, external mechanical forces lead to the activation of known mechanosensory signal transduction pathways (16,17).…”
Section: Introductionmentioning
confidence: 99%
“…For example, it has been reported that mechanosensory mutants (mec-4, mec-10) fail to navigate in short agar pillar structures. 36 Thus, it will be of interest to quantify the force exerted from such mutants and compare it with the forces exhibited by wild type C. elegans reported here. The comparison should provide new insight into the connection of the worm's touch receptors with the locomotion system.…”
Section: Elegans Locomotion Forces On Other Substratesmentioning
confidence: 91%
“…These configurations were chosen as they mimic the worm's natural environment by providing an array of obstacles used to investigate worm locomotion behaviours. 29 In addition, both configurations have been previously 36,40 compared regarding their effect on locomotion, with square-post (LC) arrays found to enhance nematode locomotion compared to hexagonal arrays. 36 For both pillar configurations, there are two different layouts for each arrangement.…”
Section: Device Designmentioning
confidence: 99%
“…This rather simple environment, though easy to implement, is insufficient to mimic the soil which is the natural habitat for C. elegans. 30 In an attempt to provide a more soil-like environment, the concept of artificial soil [30][31][32] was proposed, and "soil" of different forms was fabricated. Basically, the soil is composed of a large matrix of micro-pillars, in which the dimension and distance of pillars are varied.…”
Section: Introductionmentioning
confidence: 99%